If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 2cosx = 10 Solving 9 + 2cosx = 10 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 2cosx = 10 + -9 Combine like terms: 9 + -9 = 0 0 + 2cosx = 10 + -9 2cosx = 10 + -9 Combine like terms: 10 + -9 = 1 2cosx = 1 Divide each side by '2osx'. c = 0.5o-1s-1x-1 Simplifying c = 0.5o-1s-1x-1
| r=Ct+a | | m^2-7.5=92.5 | | 7/5y=26/15 | | ((x-3)/6)=2-x | | 3+7x^2+10=0 | | 7/5z-38/45=53/45 | | x-3/6=2-x | | 52/51/91/34 | | -16x^2+14x+13.5=5 | | -(1/2)=x^-2 | | (X-9)(x^2+5x+6)=0 | | 52/51/91:34 | | -16x+14x+13.5=5 | | 1000=16t^2+1900 | | X+50.3x-10= | | (6x+1)(2x+10)=180 | | 3(b-7)-2=3 | | (2x+10)+(6x+1)=180 | | 3f(-3)+h(5)= | | 9+-5x=4 | | -19+x=-19 | | -7(k-8)-(-8k+6)=-2 | | 20z-5-12x=10z+8 | | 1.5/6=3/x | | 0.85(x)=200 | | -7(k-8)-(-k+6)=-2 | | N*1/5=9 | | 10(2+x)=15(x+1)+15 | | -3*x+9-2x=-12-5x | | g^2+16g+59=0 | | 5(3x-2)-3(x-1)=1000 | | 4x+4-7x-2=3x-6x-11 |